La serie 467 COS.TERT.DICT.ITER. AVGVR PONT.MAX. Una nota. - Amela Valverde, Luis (Myrtia, 2025)
The article focuses on the series of denarii RRC 467, issued in favor of C. Julius Caesar in 46 BC, and discusses their geographical and chronological attribution, as well as their iconography and political significance. It is believed that this issue, which does not mention Caesar's name, may have been produced by a subordinate in a traveling mint, possibly in Africa, although there are doubts about this location. The coin features images and legends that reflect Caesar's supreme position in the State and his relationship with religion, suggesting that it was minted to finance his military campaigns and celebrate his triumphs. Additionally, the possible function of the series in political propaganda and its connection to the distribution of resources to the legions and the plebe is analyzed.